Upaya Meningkatkan Hasil Belajar Siswa Membaca Teks Dialog Bahasa Inggris dengan Metode Role Playing pada Kelas IX-5 SMP Negeri 17 Kota Tangerang Selatan - Wagini Wagini (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
This study aims to determine efforts to improve student learning outcomes in reading English dialogue texts with the role playing method of class IX-5 SMP Negeri 17 South Tangerang City. The object of the study was grade IX-5 students of SMP Negeri 17 with a total of 40 children. This action research is a collaborative action research by dividing 3 (three) important research groups. The results of the study obtained the value of learning outcomes increased by 17.4%. In cycle I the average value was 70.3 and cycle II the average value was 82.5 from the success criteria of KKM > 75. Classical completeness increased by 38% as seen from cycle I 45% and cycle II 83% from success criteria > 80%. Student activity increased by 25.9% as seen from the first cycle 65.6% and in the second cycle 91.5% of the success criteria > 70%. This Role Playing method is not the only determining factor for the success of learning to read English dialogue texts so further research needs to be done using other methods.